Peran Reviu Laporan Keuangan oleh Inspektorat terhadap Akuntablitas Laporan Keuangan : Survey pada Auditor di Inspektorat Pemerintah Sulawesi Selatan - Fachri (Insan Cita Bongaya Research Journal, 2024)
This study aims to analyze the role of financial statement review by the inspectorate on the accountability of government financial statements. The survey was conducted on auditors working at the South Sulawesi government inspectorate totaling 49 auditors. Data collection uses questionnaire techniques. Data analysis uses simple regression analysis. The results of the study show that the review of the inspectorate's financial statements has a positive and significant effect on the accountability of financial statements